2023
DOI: 10.1007/s10916-023-01954-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Continuous with Periodic Vital Sign Scoring for Clinical Deterioration Using a Patient Data Model

Abstract: To evaluate a minute-by-minute monitoring algorithm against a periodic early warning score (EWS) in detecting clinical deterioration and workload. Periodic EWSs suffer from large measurement intervals, causing late detection of deterioration. This might be prevented by continuous vital sign monitoring with a real-time algorithm such as the Visensia Safety Index (VSI). This prospective comparative data modeling cohort study (NCT04189653) compares continuous algorithmic alerts against periodic EWS in continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Barriers were technological and related to device design and internet connectivity [33 ▪ ]. The benefit of CVSM on reducing nurses workload is further supported by a descriptive analysis documenting a 10 minute per patient per day time saving with CVSM as compared with NEWS [34], and also in a case control study in 249 patients of CSVM vs manual monitoring that also found decreased time to rapid response team activation [35], similar to other aforementioned studies [6,19].…”
Section: Implementation Facilitators and Barrierssupporting
confidence: 52%
See 3 more Smart Citations
“…Barriers were technological and related to device design and internet connectivity [33 ▪ ]. The benefit of CVSM on reducing nurses workload is further supported by a descriptive analysis documenting a 10 minute per patient per day time saving with CVSM as compared with NEWS [34], and also in a case control study in 249 patients of CSVM vs manual monitoring that also found decreased time to rapid response team activation [35], similar to other aforementioned studies [6,19].…”
Section: Implementation Facilitators and Barrierssupporting
confidence: 52%
“…AI applications for continuous monitoring is already reported to have benefit within alert reduction [8 ▪ ], early detection (sometimes termed prediction) [6,18], pattern recognition by combining multisensor and additional sources of information (i.e., blood-samples, demographics etc.) [18,19], and will undoubtedly venture into new areas.…”
Section: Attempts To Implement Continuous Vital Sign Monitoring With ...mentioning
confidence: 99%
See 2 more Smart Citations